A novel phytoremediation technology for polluted cadmium soil: Salix integra treated with spermidine and activated carbon. (November 2022) - Yin, Zerun; Yu, Jinpeng; Han, Xinran; Wang, Hui; Yang, Quangang; Pan, Hong; Lou, Yanhong; Zhuge, Yuping
Abstract: A variety of plants have been used as phytoremediation materials to remove Cd from polluted soil. However, the disadvantages of using plants for decontamination include low biomass, low uptake, and inefficiency. We conducted experiments to determine the effects of spermidine and activated carbon treatments of Salix integra on Cd removal. The results showed that exogenous spermidine and activated carbon increased plant growth and root development compared with the CK. The increased dry mass (39.65–92.95%) with the combined spermidine and activated carbon treatments was higher than that with either single treatment (14.79–62.80%). The root length, surface area, root volume, and root diameter with the combined spermidine and activated carbon treatments (53.51–189.35%, 113.08–207.62%, 111.71–499.27%, and 32.51–106.62%, respectively) were higher than those of the lone application treatments (19.35–132.23%, 52.33–111.57%, 35.08–297.07%, and 24.22–81.38%, respectively). In addition, spermidine and activated carbon application reduced the toxicity of Cd to S. integra by improving the antioxidant capacity, thereby increasing the accumulation of Cd. The application of spermidine and activated carbon also changed the distribution of Cd in each part of S. integra. There was increased accumulation of Cd in the shoots and better absorption by the S. integra shoots, thereby improving their Cd remediation efficiency. The combined 0.8 mM spermidine and 0.5 g kg −1 activated carbon were most effective on removing Cd from the soil. The Cd removal efficiency was 78.11–120.86% higher than that of the CK. Our results may provide foundational information for understanding the mechanisms for the sustainable remediation of Cd-contaminated soil using a combination of spermidine and activated carbon. Graphical abstract: Image 1 Highlights: Effects of spermidine and activated carbon treatment of Salix integra on Cd removal. Plant growth and development were increased compared with the control. Cd toxicity to S. integra was reduced as the antioxidant capacity was improved. Cd removal efficiency was 78.11–120.86% higher than that of the control. This novel strategy might help understand the mechanisms of sustainable remediation.